MENGHADAPI TEKANAN KERJA DI SEKTOR PERBANKAN: TINJAUAN HUKUM DAN STRATEGI KOMUNIKASI DALAM MENGELOLA STRES KARYAWAN - AAA Ngurah Sri Rahayu Gorda; Sahri Aflah Ramadiansyah; I Putu Dharmawan Pradhana; I Wayan Abimayu Angga Nugraha (Media Bina Ilmiah, 2024)
This study explores the work pressure experienced by employees at National Bank in Denpasar City and the strategies used to deal with it. Using a qualitative approach, data were obtained through in-depth interviews and observations of six informants, including marketing employees and a psychologist. The results show that although work pressure has a significant impact on performance, employees can manage stress through leave, physical activity, and social support. The balance between work and personal life is key to reducing the intention to move jobs. This study also links aspects of banking law and marketing communication, emphasizing the importance of a supportive work environment and effective communication in improving employee performance. These results provide insight for bank management to create better strategies for supporting employee welfare and increasing organizational productivity.